Analysis and Design of Web-Based Database Application for Culinary Community - Huda, Choirul; Awang, Osel Dharmawan; Raymond, Raymond; Raynaldi, Raynaldi (ComTech: Computer, Mathematics and Engineering Applications, 2017)
This research is based on the rapid development of the culinary and information technology. The difficulties in communicating with the culinary expert and on recipe documentation make a proper support for media very important. Therefore, a web-based database application for the public is important to help the culinary community in communication, searching and recipe management. The aim of the research was to design a web-based database application that could be used as social media for the culinary community. This research used literature review, user interviews, and questionnaires. Moreover, the database system development life cycle was used as a guide for designing a database especially for conceptual database design, logical database design, and physical design database. Web-based application design used eight golden rules for user interface design. The result of this research is the availability of a web-based database application that can fulfill the needs of users in the culinary field related to communication and recipe management.